A taxonomic study on the angiosperm flora of Trishal Upazila, Mymensingh - Rahman, M Oliur; Alam, Md Tauhidul (Dhaka University Journal of Biological Sciences, 2013)
Trishal Upazila has been floristically explored to make an inventory, identify and document the angiosperm flora. A total of 209 species under 171 genera and 69 families have been identified. Magnoliopsida (Dicots) is represented by 163 species distributed in 133 genera and 54 families, and Liliopsida (Monocots) is constituted by 46 species under 38 genera and 15 families. In Magnoliopsida Asteraceae with 12 species and in Liliopsida Poaceae with 11 species is found as the largest family. The genus Ficus and the genus Fimbristylis stand the first position, respectively in dicots and monocots. Herbs are represented by 124 species, shrubs by 36 species and trees by 49 species. Dhaka Univ. J. Biol. Sci. 22(1): 63-74, 2013 (January)